Does Academic Preparedness Influence Performance? A Comparative Study Across Programs At Politeknik eLBajo Commodus - I Wayan Pio Pratama (JURNAL AKADEMISI VOKASI, 2024)
This study investigates academic performance variations across study programs at Politeknik eLBajo Commodus, blending quantitative analysis with qualitative insights to provide a holistic view of student achievement. Employing an Analysis of Variance (ANOVA) on 'Tes Bakat Skolastik' scores, we sought to identify significant differences in academic performance among the programs. Additionally, casual interviews with students were conducted to explore their perceptions of program selection, academic preparedness, and the challenges encountered. Our methodology combined statistical rigor with a nuanced understanding of student experiences, offering a comprehensive analysis of the factors influencing academic success. The quantitative phase involved comparing mean scores across programs using ANOVA, while the qualitative phase entailed gathering subjective insights from students regarding their academic journey and preparation. The results revealed no statistically significant differences in performance across study programs, indicating a baseline uniformity in academic achievement. However, student interviews highlighted a significant gap in pre-admission knowledge about program expectations and personal academic readiness. These findings suggest the need for enhanced pre-enrollment assessments and orientation programs to better align student expectations with academic demands. In conclusion, this study underscores the importance of a holistic educational approach that encompasses both statistical analyses and the lived experiences of students, advocating for initiatives that support informed decision-making and academic preparedness at the tertiary level.